INVESTIGATING THE ENTREPRENEURIAL SKILLS OF VHS STUDENTS: LEVEL, FORMATION AND READINESS - Sapitri Januariyansah; Dwiki Muda Yulanto; Safri Gunawan; Efri Meldianto; Didik Rohmantoro (Program Studi Pendidikan Teknik Mesin Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwiajaya, 2025)
Since the 4.0 industry, the work in industry has been largely replaced by computer-based labor and robots. This can lead to the reduction of human labor in the industry. Equip prospective workers with 21st century skills were the alternative solutions by stakeholders. However, such skills may not necessarily guarantee a person to get a job in the industry. So the students need to have entrepreneurial skills as another solution. This study aims to reveal the readiness of the students in work and entrepreneurship through these skills. The type of research used was Sequential Explanatory Design with Mixed Method Approach. The sampling technique used was Multistage Sampling that was by Cluster Random Sampling to choose the school and the class, then Proportionate Random Sampling to select the students. The data collection techniques used questionnaires and interviews. The content validity technique used was with expert judgment, while the construct validity used is with Confirmatory Factor Analysis (CFA). The data analysis technique used descriptive technique. The results showed that the level of entrepreneurship skills of the students in general fall into the high category (Mean Ideal 2.5 < Mean Value) with the details of each of which are Self-Management (3.387), Teamwork (3.243), technology (3.186), Communication (3.162), Problem Solving (2.986), Planning and Organizing (2.986), and Initiative and Enterprise (2.923). This was reinforced by the results of interviews that indicated the existence of efforts to form entrepreneurial skills through learning and activities in the schools. The entrepreneurial skills were a one of the alternatives to prepare the students in the 4.0 industry.